Physical environmental impacts of island tourism development: a case study of Pangkor Island - Diana Mohamad; S. Rahman; Azizi Bahauddin; Badaruddin Mohamed (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
It is readily accepted that island destinations and nature based settings are fragile in encountering the physical environment impacts induced by tourism development although this still depends very much on such variables as the intensity of the development, the intensity of activities and the background of the visitors. This study analysed Pangkor Island residents’ perception of physical environment impacts induced by tourism development in particular with regard to perceived biodiversity issues. A total of 268 respondents was sampled in a field questionnaires survey. The finding revealed that the majority of local residents who were largely dependent tourism for their were gravely concerned with the physical environmental impacts of the tourism development, in particular, with respect to scuba diving and snorkeling activities. The negative environmental impacts were perceived to be largely due to the lack of experience on the part of guest snorkelers and the intensity of the snorkeling activities at certain sites.